Leadership in Pediatric Surgery from a Senior's Perspective - Tovar, Juan A. (European Journal of Pediatric Surgery, 2017)
Management of a pediatric surgical group involves organization, coordination, and direction of human resources in an attempt to achieve the best results in an efficient way. However, true leadership of such group should also involve inspiring it with a purpose. The superior interest of the patients and their families will be better served by achieving excellence at all levels of care, research, teaching, and diffusion of the results. These values are the core of the leader's action and may be difficult to develop in a hospital framework in which the main decisions are not always into his/her hands.This review summarizes a theory on leadership at large and then analyzes in detail the peculiarities that distinguish surgical and pediatric surgical departments from a corporation in an attempt to extend the application of the principles of leadership to these structures.Finally, the steps possibly taken by prospective leaders toward achieving that condition and some tips for the candidates based on the personal experience of the author are advanced.
Keywords: leadership; pediatric surgery; surgery; value; purpose; management; nontechnical skills